AWARENESS ABOUT ORAL CANCER AMONG DENTAL STUDENTS - R, Nishanthi; Velayudhan, Ashok; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Introduction Oral cancer affects people in the 6th and 7th years of existence with a background marked by smoking tobacco and/or liquor utilization. Early acknowledgment and referral is basic, as less treatment is required to decrease mortality and morbidity Past examinations have demonstrated that oral cancer can be quiet in symptoms, with attention to primal signs being increasingly advantageous in diagnosis. Aim: To assessing oral cancer knowledge and awareness among undergraduate dental students Materials and method: A cross-sectional survey was done with a self-administered questionnaire with 10 questions circulated among 100 dental students. The questionnaire assessed the awareness about oral cancer, its risk factors, clinical manifestations, diagnosis, and management strategies. The responses were recorded and analyzed. Results: 96 % of dental students were aware of oral cancer. 95% said smoking and tobacco-related products are the major risk factors of oral cancer. 85% were aware of the clinical manifestation of oral cancer. 71% were aware of the diagnosis of oral cancer, and 65% were aware of management strategies for oral cancer. Conclusion: The greater part of the responders in this investigation had satisfactory information about clinical indications of oral cancer. Efforts ought to be made to develop an inspirational disposition towards avoidance of oral cancer. There is a necessity to present instructions on counteraction, early referral, and demonstrative techniques for oral cancer .